2020
DOI: 10.2495/cmem-v8-n3-220-232
|View full text |Cite
|
Sign up to set email alerts
|

Development of a computational fluid dynamics simulation tool for lubrication studies on cycloidal gear sets

Abstract: In the last decades, the growing mechatronic sector has promoted the development of more and more compact and efficient gearboxes. The margins of improvement are still big even if, sometimes, finding the optimal solutions is a trial and error procedure. For this reason, the development of dedicated tools for the optimization of the geometry and configuration of gearboxes can significantly increase the development effectiveness and help in reducing design costs. Moreover, having a more efficient solution could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the realm of precision machinery, attention is consistently directed toward the performance and efficiency of transmission systems, as underscored by a wealth of scholarly inquiry [1,2]. Gears, pivotal mechanical components within these systems, are recognized as bearing a substantial portion of the power load [3][4][5][6][7][8][9][10][11][12][13]. It has been observed that during their operation, the heat generated from interactions such as meshing, sliding, and impact with adjacent gears plays a significant role in influencing the system's stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of precision machinery, attention is consistently directed toward the performance and efficiency of transmission systems, as underscored by a wealth of scholarly inquiry [1,2]. Gears, pivotal mechanical components within these systems, are recognized as bearing a substantial portion of the power load [3][4][5][6][7][8][9][10][11][12][13]. It has been observed that during their operation, the heat generated from interactions such as meshing, sliding, and impact with adjacent gears plays a significant role in influencing the system's stability and efficiency.…”
Section: Introductionmentioning
confidence: 99%